2020
DOI: 10.1002/art.41485
|View full text |Cite
|
Sign up to set email alerts
|

Effects of BAFF Neutralization on Atherosclerosis Associated With Systemic Lupus Erythematosus

Abstract: Objective Cardiovascular disease (CVD) is the leading cause of death in systemic lupus erythematosus (SLE). B cells play a key role in the pathogenesis of lupus, and anti‐BAFF therapy has been approved for use in SLE. Since mature B cells also promote atherosclerosis, we undertook this study to evaluate, in a mouse model and in SLE patients, whether BAFF neutralization has an atheroprotective effect in SLE. Methods The effect of BAFF on atherosclerosis associated with lupus was investigated in the atherosclero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…The increased amount of foamy cells secrete inflammatory cytokines leading to atherosclerotic plaque vulnerability that may lead to higher risk of hemorrhage/rapture 5 . Increased evidence has documented that the abundance of foamy macrophages within plaques is correlated with the decades-long lasting asymptomatic pathogenesis of AS in the clinic 6 , 7 . Therefore, accurately identifying the vulnerable atherosclerotic plaques (VASPs) in the early stage of AS, assessing the risk of acute coronary syndrome, and taking effective interventions are essential to prevent the occurrence of life-threatening events.…”
Section: Introductionmentioning
confidence: 99%
“…The increased amount of foamy cells secrete inflammatory cytokines leading to atherosclerotic plaque vulnerability that may lead to higher risk of hemorrhage/rapture 5 . Increased evidence has documented that the abundance of foamy macrophages within plaques is correlated with the decades-long lasting asymptomatic pathogenesis of AS in the clinic 6 , 7 . Therefore, accurately identifying the vulnerable atherosclerotic plaques (VASPs) in the early stage of AS, assessing the risk of acute coronary syndrome, and taking effective interventions are essential to prevent the occurrence of life-threatening events.…”
Section: Introductionmentioning
confidence: 99%
“…In SLE, CD163 + macrophages have been implicated in the pathogenesis of lupus nephritis [2]. High sCD163 level in serum may thus reflect the involvement of CD163 + macrophages in both atherosclerosis and SLE and indicate the implication of SLE immune dysregulation in atherosclerotic inflammatory process [7, 8]. In our cohort, sCD163—known to be coupled with impaired insulin sensitivity and obesity [9]—was associated with BMI.…”
Section: Figmentioning
confidence: 90%
“…[ 147 , 148 ] Recent data in a mouse model of lupus and atherosclerosis found that BAFF inhibition improved atherosclerosis lesions in mice with low plasma cholesterol levels but worsened the lesions in mice with high cholesterol levels. [ 149 ]…”
Section: Sle-specific Inflammation and Mechanisms Of Atherosclerosismentioning
confidence: 99%